The mangrove flora and their physical habitat characteristics in Bunaken National Park, North Sulawesi, Indonesia - RIGNOLDA DJAMALUDDIN (Biodiversitas Journal of Biological Diversity, 2018)
Djamaluddin R. 2018. The mangrove flora and their physical habitat characteristics in Bunaken National Park, North Sulawesi, Indonesia. Biodiversitas 19: 1303-1312. The mangrove forests of Bunaken National Park are among the most distinctive and unusual in Southeast Asia because of the species that the forests contain. This study investigated the identity and diversity of mangrove plants as well as physiographic factors and major physical processes of every type of sub-habitats. Seven surveys were conducted to collect and identify mangrove species of the park. Sub-habitats where specimen was found, aspects related to tidal inundation, nature of soil, freshwater influence and topography were observed as well as major physical processes influencing the condition of each sub-habitat. The results suggested that the park was floristically rich with at least 27 plant species and they were distributed over ten recognized sub-habitat types in different composition and diversity. Ceriops zippeliana Blume, Lumnitzera racemosa Willd, Lumnitzera littorea (Jack) Voigt., Sonneratia ovata Backer, and Camptostemon philippinense (Vidal) Becc. were found in Bunaken National Park and their presence confirmed the broader distribution limit of these species within Indo-Malesia region. A special notice was for C. philippinense as the distribution limit of this is rarely reported.